Networks and connections in legal history / edited by Michael Lobban, Ian Williams. - Lobban, Michael; Williams, Ian Scott, 1981- (Cambridge University Press, 2017)
Network and Connections in Legal History examines networks of lawyers, legislators and litigators, and how they shaped legal development in Britain and the world. It explores how particular networks of lawyers - from Scotland to East Florida and India - shaped the culture of the forums in which they operated, and how personal connections could be crucial in pressuring the legislature to institute reform - as with twentieth century feminist campaigns. It explores the transmission of legal ideas; what happened to those ideas was not predetermined, but when new connections were made, they could assume a new life. In some cases, new thinkers made intellectual connections not previously conceived, in others it as the new purposes to which ideas and practices were applied which made them adapt. This book shows how networks and connections between people and places have shaped the way that legal ideas and practices are transmitted across time and space.